What Do Industry-Specialist Auditors Know? - Solomon, Ira; Shields, Michael D.; Whittington, O. Ray (Journal of Accounting Research, 1999)
Stable URL:http://links.jstor.org/sici?sici=0021-8456%28199921%2937%3A1%3C191%3AWDIAK%3E2.0.CO%3B2-FJournal of Accounting Research is currently published by The Institute of Professional Accounting, Graduate School ofBusiness, University of Chicago.Your use of the JSTOR archive indicates your acceptance of JSTOR's Terms and Conditions of Use, available athttp://www.jstor.org/about/terms.html. JSTOR's Terms and Conditions of Use provides, in part, that unless you have obtainedprior permission, you may not download an entire issue of a journal or multiple copies of articles, and you may use content inthe JSTOR archive only for your personal, non-commercial use.Please contact the publisher regarding any further use of this work. Publisher contact information may be obtained athttp://www.jstor.org/journals/grad-uchicago.html.Each copy of any part of a JSTOR transmission must contain the same copyright notice that appears on the screen or printedpage of such transmission.The JSTOR Archive is a trusted digital repository providing for long-term preservation and access to leading academicjournals and scholarly literature from around the world. The Archive is supported by libraries, scholarly societies, publishers,and foundations. It is an initiative of JSTOR, a not-for-profit organization with a mission to help the scholarly community takeadvantage of advances in technology. For more information regarding JSTOR, please contact support@jstor.org.http://www.jstor.orgFri Jan 4 16:36:17 2008